Analisis Penentuan Harga Jual Dalam Meningkatkan Laba Pada Usaha Ayam Geprek Di Batanghari Kabupaten Lampung Timur - Maisa, Dinda; Mentari, Mentari; Destriani, Nazwa Naila; Nabilla, Nabilla; Carmidah, Carmidah (Maisyatuna, 2024)
UMKM play a crucial role in the national economy as primary contributors to economic activities. According to BPS data, approximately 1.5 million Indonesian MSMEs operate in the food sector. The aim of this research is to understand the determination of selling prices to optimize business profits, considering production costs, operational expenses, and other factors. The research employs a qualitative approach, utilizing primary data collected directly by the researcher. Analyzing all costs incurred in the production of "Ayam Geprek" at Lesehan Lala, the findings indicate that the establishment's pricing strategy does not maximize profits. Lesehan Lala sets its selling prices based on market rates without considering the overall production costs, operational expenses, and other relevant factors.